Bank’s Characteristics of Cross-Border Acquisition and Domestic - Dhiyan Amirah Shora (Management and Sustainable Development Journal, 2021)
This study aims to examine the differences in the characteristics of foreign (cross-border) and domestic acquisition target banks in the period 2011 – 2020 in Indonesian banking, where there are 20 mergers and acquisitions transactions of local banks by foreign (cross-border) and domestic banks resulting in the transfer of ownership of 10 local banks from domestic ownership to foreign ownership. The data in this study were obtained from the Komisi Pengawas Persaingan Usaha (KPPU) and the annual reports of each bank. The methodology used is descriptive statistics and student t test. The results showed that: (i) capital, profitability performance, credit quality and cost efficiency of foreign acquisition target banks were better than domestic acquisition target banks; (ii) however, the liquidity of domestic target banks is better than foreign acquisition target banks.